Operational Concepts for Urban Air Mobility deployment in the next decades - Vito, V. Di; Dziugiel, B.; Melo, S.; Thije, J.T. ten; Duca, G.; Liberacki, A.; Hesselink, H.H.; Giannuzzi, M.; Menichino, A.; Witkowska-Koniecz, A. (IOP Publishing, 2022)
SustainabilityRecommendations for Efficient Deployment of UAM) project has been funded by H2020 andis ongoing, with the main objective of providing cities with knowledge concerning deploymentof UAM services and definition of necessary standards and recommendations assuringcommon acceptance, safety and sustainability within integrated metropolitan transport systemfor three time horizons (2025, 2030 and 2035). In the project, dedicated activities have beencarried out to develop operational concepts for Urban Air Mobility (UAM) deployment in thenext decades. The main results from these activities are presented in this paper, which namelyincludes the main project outcomes in terms of: the identification of the most relevant andpromising technologies that can enable the UAM implementation over the next decades, takinginto account the current technological trends and perspectives; the outline of the regulatoryframework in which the UAM will be shaped in the next decades; the definition of the mostrelevant aspects and constraints affecting the UAM deployment from the point of view ofintegration of such new mobility form in the cities infrastructures; the outline of the foreseenUAM concept of operations and definition of the most relevant use case that are expected to beimplemented in the cities over the three time horizons considered in the project, i.e. 2025, 2030 and 2035.